2012
DOI: 10.1159/000334901
|View full text |Cite|
|
Sign up to set email alerts
|

The Antioxidant N-Acetylcysteine Prevents the Mitochondrial Fragmentation Induced by Soluble Amyloid-F Peptide Oligomers

Abstract: Background: Soluble amyloid-F peptide oligomers (AFOs), which are centrally involved in the pathogenesis of Alzheimer’s disease, trigger Ca2+ influx through N-methyl-D-aspartate receptors and stimulate reactive oxygen species generation in primary hippocampal neurons. We have previously reported that AFOs promote Ca2+ release mediated by ryanodine receptors (RyR), which in turn triggers mitochondrial fragmentation. We have also reported that the antioxidant N-acetylcysteine (NAC) prevents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…Recent evidence has revealed that Aβ oligomers, which are recognized as one of the most toxic forms of the Aβ peptide, interfere with mitochondrial dynamics (Hefti et al, 2013;Sanmartin et al, 2012). Overexpression of Aβ in M17 cells affects the expression of different proteins involved in mitochondrial fission and fusion, such as DLP1, Fis1, and OPA1 (Wang et al, 2008).…”
Section: Mitochondrial Dysfunction and Iron Accumulation In Admentioning
confidence: 99%
“…Recent evidence has revealed that Aβ oligomers, which are recognized as one of the most toxic forms of the Aβ peptide, interfere with mitochondrial dynamics (Hefti et al, 2013;Sanmartin et al, 2012). Overexpression of Aβ in M17 cells affects the expression of different proteins involved in mitochondrial fission and fusion, such as DLP1, Fis1, and OPA1 (Wang et al, 2008).…”
Section: Mitochondrial Dysfunction and Iron Accumulation In Admentioning
confidence: 99%
“…We reported previously that amyloid β peptide oligomers (AβOs) induce anomalous Ca 2+ signals in primary hippocampal neurons; these signals arise initially from Ca 2+ entry through N -Methyl- D -aspartate (NMDA) receptors and are subsequently amplified via RyR channels co-stimulated by Ca 2+ entry signals and the increased ROS levels produced by AβOs (Paula-Lima et al, 2011; SanMartín et al, 2012a). Furthermore, the levels of RyR2, which is the most abundant RyR isoform expressed in the brain (Giannini et al, 1995), are 20% lower in the brain from AD cases compared to controls (Kelliher et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the mitochondrial Ca 2+ uniporter complex mediates mitochondrial Ca 2+ uptake following RyR activation in cardiac muscle fibrils (Szalai et al, 2000) and IP 3 R-mediated Ca 2+ release in liver (Csordas et al, 2006). Intracellular Ca 2+ channels also generate Ca 2+ signals that affect the mitochondrial network in neurons, since the selective RyR agonist 4-chloro-m-cresol (4-CMC) induces mitochondrial fragmentation in neurons (SanMartín et al, 2012a), indicating that Ca 2+ release from the ER has a pivotal role in shaping mitochondrial dynamics in hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, AbOs induce oxidative stress (De Felice et al 2007), promote excitotoxicity (Alberdi et al 2010) and cause a swift and prolonged increase in intracellular Ca 2? concentration (Paula-Lima et al 2011;SanMartin et al 2012).…”
Section: Introductionmentioning
confidence: 99%